Information transfer as a tool to improve the resilience of farmers against the effects of climate change: The case of the Peruvian National Agrarian Innovation System - Ramos Sandoval, Rosmary (2022)
CONTEXT: In the last few years, the effects of climate change have impacted heavily on the agricultural sector, particularly in developing countries provided their high vulnerability. In this sense, knowledge and information transference could act as a strategic support service to improve the resilience of their farming systems, as this would help farmers to adapt and take advantage of the new scenarios brought by climate change, as well as to take preventive actions. OBJECTIVE: The aim of this study was to understand the structure of the interactions between farmers and institutions of the National Agrarian Innovation System of Peru regarding the transfer of information on preventing the effects of extreme weather events. To do so, we aim to understand how farmers and institutions are connected and how the climatic and farming systems' particularities of the territories, the main roles of the institutions and the media through which farmers get the information from each of them could influence such information transfer processes.